Development Of A Pencak Silat Sickle Kick Training Model: This Research Focuses On The Ability To Kick Speed - Sitompul, Surya Rezeki; Aisah, Siti Nur (Jurnal Pendidikan Jasmani (JPJ), 2024)
This research and development paper was created to provide an updated product from previous research in the form of a product “Development of Pencak Silat Scythe Kick Training Model: This Research Focuses on Kick Speed Ability” that can serve as a reference for coaches in providing training models for athletes and also as a reference tool for independent learning/training athletes. The results have shown that this sickle kick training model is readily implementable. Based on the average results of the evaluation of experts, namely martial arts experts, experienced martial artists and exercise experts, the results are 98% and fall into the category of worthy of application and are supported by the results of the pretest post test pretest correlation Pearson 1 .997** Sig. (2-tailed) ,003 N 4 4 Posttest Pearson correlation ,997** 1 Sig. (2-tailed) ,003 N 4 4**. The correlation is significant at the level of 0.01 (2-tailed). From the above results, the results of the pretest and posttest on the ability of sickle kick speed that was conducted produce a correlation value of 0.997> 0.959, it is found that there is a relationship between the Pencak Silat sickle kick training model and the ability to kick speed, with a significant value of 0.003 <0.05. This means that H0 is rejected and Ha is accepted, which means that there is a positive relationship in the kick training model aimed at kick agility on the ability to kick sickle kick speed in martial arts.